2013
DOI: 10.1002/pssb.201349180
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent photoluminescence studies in CsI:Tl films with varying thicknesses

Abstract: Films of Tl doped CsI in the 10 nm to 3 µm thickness range were deposited on silicon substrates using the physical vapor deposition technique under vacuum conditions. The films exhibited a columnar growth behavior with a preferential orientation along 〈200〉. The photoluminescence (PL) properties of the deposited films were studied in the 77–300 K temperature range and found to be significantly different compared to the bulk CsI:Tl single crystal. In the excitation process, the unperturbed self trapped exciton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Compared to reported spectra of Tl-doped halides, the luminescence peaks at around 400 and 580 nm were attributed to 3 P 1 → 1 S 0 transitions of Tl + and the off-center STEs localized around Tl + , respectively. [42][43][44] By increasing Tl concentration, the luminescence peak around 400 nm looked slightly shifted to a longer wavelength. As seen in Fig.…”
Section: Pl Propertiesmentioning
confidence: 99%
“…Compared to reported spectra of Tl-doped halides, the luminescence peaks at around 400 and 580 nm were attributed to 3 P 1 → 1 S 0 transitions of Tl + and the off-center STEs localized around Tl + , respectively. [42][43][44] By increasing Tl concentration, the luminescence peak around 400 nm looked slightly shifted to a longer wavelength. As seen in Fig.…”
Section: Pl Propertiesmentioning
confidence: 99%
“…Fedorov et al [5] fabricated CsI(Tl) layers on LiF and glass substrates, and examined their scintillation efficiency, crystal structure and spatial resolution. Shinde et al [6] deposited CsI(Tl) films on silicon substrate in the thickness range between 10 nm and 3 µm , and focused on the temperature dependent *Supported by National Key Scientific Instrument and Equipment Development Project (2011YQ03011205, 2013YQ03062902) and Key Program of the National Natural Science Foundation of China (U1332202) 1) E-mail: qinxb@ihep.ac.cn Submitted to 'Chinese Physics C' photoluminescence of CsI(Tl) films. Yao et al [7] fabricated CsI(Tl) films on glass substrate covered by a pre-deposited CsI layer, and concluded that the performance could be improved when films were prepared on substrates with special treatment.…”
Section: Introductionmentioning
confidence: 99%